PROCEDURE OF ANALYSIS SERVICE DATABASE SYSTEM TIME COMPUTER NETWORK BASED ON ONLINE BANKING - Hikmayanti Hikmayanti; Latifah. Dra. MM Latifah. Dra. MM (Jurnal Sistem Informasi, 1998)
A bank to serve customers primarily in deposit services require an online computernetwork.In this case the deposit is still using a stand alone computer that is online, therefore,used an online computer network and then analyze how the way the proceduredatabase system of computer network-based deposit service online. Another obstaclethat may arise such as the use of human resources who lack expertise and technologythat are no longer able to compete in speed and accuracy of information generated.